Entwicklung eines mesoskopischen Modells zur Abbildung von Größeneffekten in der Kaltmassivumformung mit Methoden der FE-Simulation - Geißdörfer, Stefan (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2010)
With considering the microstructure, the mesoscopic model developed in this study is able to map size dependent forming behaviour to the simulation results by using finite element method. The knowledge of the local deformation behaviour enables a size-dependent design of the deformation process as well as the calculation of size-dependent process scatte